Morphofunctional properties of stromal stem cells incubating in vitro under dynamic conditions - I. V. Zapuskalov; O. I. Krivosheina; I. A. Khlusov; Ya. A. Martusevich; N. M. Shevtsova; K. V. Zaytsev; O. B. Kochmala (Бюллетень сибирской медицины)
The culture of stromal stem cells was incubated under constant and dynamic conditions. The incubation period was lasting 48 h. Intracellular enzyme activity of stromal stem cells were carried out with cytochemical methods. Alkaline phosphatase activity was increased under dynamic conditions, differentiation of stromal stem cells being accelerated comparatively steady-state conditions.